MAT084: Mathematics II (Basic) / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (2023)
The course is prepared to enhance the comprehension of mathematics concepts at SPM level in order to gear up students to follow the courses at diploma level.